2023
DOI: 10.1021/jacs.2c11499
|View full text |Cite
|
Sign up to set email alerts
|

Turning Red without Feeling Embarrassed─Xanthenium-Based Photocages for Red-Light-Activated Phototherapeutics

Abstract: Herein, we present high-yielding, concise access to a set of xanthenium-derived, water-soluble, low-molecular-weight photocages allowing light-controlled cargo release in the green to red region. Very importantly, these new photocages allow installation of various payloads through ester, carbamate, or carbonate linkages even at the last stage of the synthesis. Payloads were uncaged with high efficiency upon green, orange, or red light irradiation, leading to the release of carboxylic acids, phenols, and amines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…More recently, it was shown that irradiating porphyrin PPGs ( 16 in Figure ) can photorelease substrates using red wavelengths (up to 640 nm) . During revisions of this Perspective, a report on a highly promising class of visible light absorbing xanthenium PPG platform was also published . Nevertheless, for a simple organic photocage that retains the “plug-and-play” simplicity of the nitrobenzyl photocages, that requires no carrier to cross the cell membrane, that works both in the presence and absence of oxygen, but that strongly absorbs single photons of 600–700 nm light, BODIPY photocages such as 17 – 19 (Figure ) represent an exceptionally attractive PPG platform.…”
Section: Absorption Properties Of Bodipy Photocagesmentioning
confidence: 99%
“…More recently, it was shown that irradiating porphyrin PPGs ( 16 in Figure ) can photorelease substrates using red wavelengths (up to 640 nm) . During revisions of this Perspective, a report on a highly promising class of visible light absorbing xanthenium PPG platform was also published . Nevertheless, for a simple organic photocage that retains the “plug-and-play” simplicity of the nitrobenzyl photocages, that requires no carrier to cross the cell membrane, that works both in the presence and absence of oxygen, but that strongly absorbs single photons of 600–700 nm light, BODIPY photocages such as 17 – 19 (Figure ) represent an exceptionally attractive PPG platform.…”
Section: Absorption Properties Of Bodipy Photocagesmentioning
confidence: 99%
“…103 Most recently, Bojtár and coworkers developed a group of xanthenium dyes that could absorb NIR light for prodrug activation in cells. 104…”
Section: Physical Stimuli-induced Chemistry For Prodrug Activationmentioning
confidence: 99%
“…103 Most recently, Bojta ´r and coworkers developed a group of xanthenium dyes that could absorb NIR light for prodrug activation in cells. 104 Simple BODIPY chromophores typically have narrow absorption bands in the visible range (l max E 490-540 nm). 105,106 However, Winter and coworkers developed a series of BODIPY derivatives with a broad absorption range, approximately 600-1000 nm (Table 5, entry 14).…”
Section: Nir Light-induced Cleavage Chemistrymentioning
confidence: 99%
“…8–14 Very recently, Bojtàr's group reported xanthenium-type PPGs that can be controlled with visible light (>540 nm) and demonstrated an application for caging an anticancer reagent, SN38. 15…”
Section: Introductionmentioning
confidence: 99%